PENGARUH SERTIFIKAT BANK INDONESIA SYARIAH (SBIS), INDEKS HARGA SAHAM GABUNGAN (IHSG), DAN NILAI TUKAR RUPIAH TERHADAP NILAI AKTIVA BERSIH (NAB) DANAREKSA SYARIAH BERIMBANG - Muhammad Rizki Aulia (Universitas Islam Negeri Sumatera Utara, 2015)
The purpose of this study is to determine the factors that influence the growth of the Net Asset Value (NAV) of a mutual fund sharia, namely Sharia Bank Indonesia Certificates (SBIS), Composite Stock Price Index (CSPI) and Exchange Rate (USD). All of the factor are assumed have significant impact on the net asset value (NAV). Danareksa Syariah Berimbang of PT. Danareksa Management. The research method is done by multiple regression. The results showed there is negative influence significant between Sharia Bank Indonesia Certificates (SBIS) and exchange rate, there is positive effect between the stock price index (CSPI), and the Asset Value net (NAB) Danareksa Syariah Berimbang